Characterization of fatty acid liposome coated with low-molecular-weight chitosan - Tan, H.W.; Misran, M. (2012)
Preparation of chitosan-coated fatty acid liposomes is often restricted by the solubility of chitosan under basic conditions. In this experiment, the preparation of chitosan-coated oleic acid (OA) liposomes using low molecular weight (LMW) chitosan (10 and 25 kDA) was demonstrated. These selected LMW chitosans are water soluble. The coating of the chitosan layer on OA liposomes was confirmed by its microscope images and physicochemical properties, such as zeta potential and the size of the liposomes. The "peeling off" effect on the surface of chitosan-coated OA liposomes was observed in the atomic force microscope images and showed the occurrence of the chitosan layer on the surface of OA liposomes. The size of the chitosan-coated liposomes was at least 20nm smaller than the OA liposomes, and the increase of zeta potential with the increasing amount of LMW chitosan further confirmed the presence of the surface modification of OA liposomes.